HUBUNGAN PARITAS, USIA DAN LAMA KALA II DENGAN KEJADIAN PERDARAHAN POST PARTUM DI PUSKESMAS AMBULU KABUPATEN JEMBER TAHUN 2012 - Dinar Perbawati (Jurnal Kesehatan dr. Soebandi, 2014)
Postpartum hemorrhage is bleeding that occurs within 24 hours after the birth to go Parity, age and duration of the second stage are the factors that influence the occurrence of cases of postpartum hemorrhage. Obstetric hemorrhage is technically defined as blood loss of 500 ml or more immediately after delivery. The purpose of this study was to determine the relationship of parity, age and duration of the second stage with the incidence of postpartum hemorrhage in Jember Ambulu health center in 2012. This research design using correlation studies, the retrospective approach. Populations that are experiencing maternal postpartum hemorrhage in health center Ambulu in 2012 a number of 64, the sample used by 55 samples. The sampling technique used was simple random sampling. From the test results data using Chi Square analysis obtained count 0.47 x2 < x2 table 5.991, meaning that there is no relationship with the incidence of maternal parity postpartum hemorrhage. Count x2 obtained at age 0.02 < 3.841 x2 table, meaning there is an association with maternal age incidence of postpartum hemorrhage. Whereas the second stage of a long relationship count obtained 4.09 x2 < x2 table 3.841, which means that the second stage of a long relationship with the incidence of maternal postpartum hemorrhage in Jember Ambulu Health Center in 2012. This fits the theory that the second stage of abnormal causes muscle failure myometrium to contract after delivery. To handle the midwife needs to improve midwifery care to pregnant women so that complications can be detected early.